Psychoendocrine Characteristics of Cadets of the Ministry of Internal Affairs - A.A. Dubinsky; E.V. Kostina; N.T. Ivashkevich; V.G. Bulygina (Психология и право, 2023)
The characteristics of 79 cadets of the Ministry of Internal Affairs (mean age — 20.3±2.3 years) were studied: 26.6% male and 73.4% female. Signs of stress, coping, level of anxiety and depression were studied. Stressful stimuli were presented by showing images of dangerous situations and incidents, as well as loud, negatively socially colored sounds. The levels of cortisol and dehydroepiandrosterone (DHEA) in saliva before and after presentation of stressful stimuli were determined. It was revealed that male cadets are characterized by high levels of cortisol and DHEA before stress, with a decrease after presentation. The group of female cadets was characterized by normal hormone indices. Profiles of reaction to stress were formed. Two pro-files were identified in the group of male cadets. The first one corresponded to destructive ways of coping with stress, depression and anxiety expression, normal dynamics of hormone indices after stress; the second one — low level of anxiety and depression, high level of coping planning-solving problems, decrease of cortisol and DHEA level after stress. For female cadets, 3 profiles were distinguished. The first was characterized by the absence of signs of stress, positive reassessment of stress, normal dynamics of hormones; the second — low level of stress, non-expressiveness of coping escape and increase of hormones after stress; the third — expression of signs of stress, coping self-control, and decrease of hormones after stress.